CircTRRAP Knockdown Has Cardioprotective Function in Cardiomyocytes via the Signal Regulation of miR-370-3p/PAWR Axis. (15th February 2022) - Zhang, Yuan; Li, Zhenggong; Wang, Jiao; Chen, Hao; He, Rui; Wu, Hongkun
Abstract : Background . Circular RNA Transformation/Transcription Domain Associated Protein (circTRRAP, hsa_circ_0081241) was abnormally upregulated in acute myocardial infarction (AMI) patients. However, its biological role and functional mechanism in AMI remain to be researched. Methods . Human cardiomyocyte AC16 was exposed to hypoxia to induce cell injury. Cell viability was detected through Cell Counting Kit-8. CircTRRAP, microRNA-370-3p (miR-370-3p), and Pro-Apoptotic WT1 Regulator (PAWR) levels were assayed by reverse transcription-quantitative polymerase chain reaction. Cell proliferation analysis was performed via 5-ethynyl-2 ′ -deoxyuridine (EdU) assay. Cell apoptosis was assessed using flow cytometry and caspase-3 activity assay. The protein levels were measured through western blot. Enzyme-linked immunosorbent assay was used to examine the release of inflammatory cytokines. Oxidative stress was assessed by the commercial kits. Dual-luciferase reporter assay, RNA immunoprecipitation, and RNA pull-down assays were performed for the validation of target interaction. Results . CircTRRAP was highly expressed following hypoxia treatment in AC16 cells. Downregulation of circTRRAP promoted cell growth but inhibited apoptosis, inflammation, and oxidative stress in hypoxic cells. CircTRRAP could target miR-370-3p, and the regulatory effects of circTRRAP on the hypoxic cells were associated with the sponge function of miR-370-3p. PAWR served as the target for miR-370-3p, and it was regulated by circTRRAP/miR-370-3p axis. The protective role of miR-370-3p was achieved by downregulating the PAWR expression in hypoxia-treated AC16 cells. Conclusion . These findings demonstrated that silence of circTRRAP exerted the protection against the hypoxia-induced damages in cardiomyocytes through regulating the miR-370-3p and PAWR levels.